Screening of fungi producing ligninolytic enzymes - Ghebreslasie, Zecarias; Premjet, Duangporn; Permjet, Siripong (Asia-Pacific Journal of Science and Technology, 2016)
A total of 61 fungi isolate were subjected for screening of ligninolytic enzyme by dye decolorization plate test. The results presented the diversity of 8 orders belonging to 17 families, 30 genera and 25 unidentified cultures. Seven families of Agaricales, three families of Polyporales, two families of Russulales and one family represent for each of the orders, Boletales, Cantharellales, Phallales, Tremellales and Xylariales. The plate test perceived seven categorical groups as: strains decolorizing a single dye implies for secreting only one of the three main enzymes ; a) Phenol red for LiP, b) Azure B for MnP c) RBBR for Lacc; strains decolorizing two of the organic colors relays for secreting only two enzymes as; d) Phenol red and Azure B, e) Phenol red and RBBR, f) Azure B and RBBR; and g) strains which decolorize three organic dyes produce three of the ligninolytic enzymes.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">